Qadhiyyat al-Riddah fi al-Islam - Agus Ghulam Ahmad; Muhammad Rizky HK (UIN Mataram, 2020)
Apostasy is one of the major sins and the greatest crimes in Islam. Rather, it is related to the principle of Islam, faith to the one God an the Prophet Muhammad. The apostate had previously believed and believed in Allah, then turned from truth to falsehood and became an unbeliever. This apostasy represents a major betrayal to the God and His Messenger. That is why God Almighty has promised to those who apostatize from his religion, the decline of deeds in this world and torment in the hereafter. The Messenger of God, may God bless him and grant him peace, promised to kill him when he said: (Whoever changes his religion, kill him). Apostasy is also measured by murder and adultery in its commentary. This article aims to explore the dialogue between ‘ulama about apostasy by describing and comparing all mazhab. Hence, the scholars differed in bringing rulings for the apostate from Islam. And every opinion has its inference, which we have mentioned for a long time. Among these different opinions regarding the punishment for apostasy between the proven and the defiant. The appointment of a person of apostasy is submitted to the judge in the court, as well as applying the punishment to him according to the judge’s judiciary after the conditions for that are met. The differences are expected to be able to bring a lot of dialogue on the table, so that in the future there will be no more tendency to commit violence against people who change their religions.